A Methods engineering study on Sterling Paper Products Enterprises, Inc. Tabing-Ilog, Marilao, Bulacan - Fulgencio, Charisma; Joson, Carlo Marx O.; Jumaquio, Jayson S. (Diliman, Quezon City College of Engineering, 1999)
Sterling Paper Products Enterprises, Inc. (SPPEI), with its Production Department based in Marilao, Bulacan, produces school items from rulers to notebooks, novelties like coin banks, cards and albums. The study is centered on one of its earliest products- photo albums. The history of the company and documentation of all its resources, processes and the human factor in work, limited to manufacture of albums are presented and discussed. Methods Study Techniques developed these procedures and eventually led the study to the establishment of relevant problems within the company. Three important problems are highlighted : (1) problem on delays, (2) problem on wastage, and (3) problem on ineffectivity of the grouping of machines. Each of these are identified and analyzed through appropriate tools. Work Measurement Techniques are further applied to deepen the study on the problems of the operations of producing albums and support the evaluation of recommendations. The Systems and Procedures are documented though the aspects are not fully scrutinized. The objectives and operations of SPPEI from Makati, Caloocan, Meycauayan, and Marilao are sufficiently discussed. The recommendation prescribed at the last part guarantees improvements for the company.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Sterling Paper Products Enterprises Incorporated; Paper industry; Systems analysis